A retrospective, Canadian multi‐center study examining the impact of prior response to abiraterone acetate on efficacy of docetaxel in metastatic castration‐resistant prostate cancer. Issue 15 (29th August 2014) - Azad, Arun A.; Leibowitz‐Amit, Raya; Eigl, Bernhard J.; Lester, Renee; Wells, J. Connor; Murray, R. Nevin; Kollmannsberger, Christian; Heng, Daniel Y.C.; Joshua, Anthony M.; Chi, Kim N.
<x xml:space="preserve">Abstract</x> BACKGROUND Questions about optimal sequencing of systemic therapy in metastatic castration‐resistant prostate cancer (mCRPC) and whether cross‐resistance occurs between different drugs remain largely unanswered. Previous studies have produced conflicting data on the activity of docetaxel in patients who did not attain a prostate‐specific antigen (PSA) response to abiraterone acetate (abiraterone). We investigated whether the biochemical response to abiraterone is associated with efficacy of subsequent docetaxel therapy. METHODS mCRPC patients treated with docetaxel after abiraterone were retrospectively identified at three Canadian institutions. Patients who had also received docetaxel prior to abiraterone were termed "docetaxel‐experienced, " while those not treated with docetaxel prior to abiraterone were termed "docetaxel‐naïve." Treatment outcomes on docetaxel were stratified by prior response to abiraterone and compared using χ2‐square test for confirmed PSA response rate (≥ 50% decline from baseline maintained for ≥ 3 weeks) and the log‐rank method for progression‐free survival (PFS) and overall survival (OS). RESULTS Eighty‐six patients were treated with abiraterone, of whom 49 were docetaxel‐experienced and 37 were docetaxel‐naïve. Prior PSA response to abiraterone was no decline, <50% decline and ≥ 50% decline in 37%, 26%, and 37% of patients respectively. The overall PSA response rate to docetaxel was 34.9%, median PFS was 4.0 months and median OS was 11.66 months. Notably, no differences were seen in confirmed PSA response rates (38% vs. 36% vs. 31%, P = 0.86), median PFS (4.04 months vs. 3.94 months vs. 4.24 months, P = 0.43) and median OS (11.86 months vs. 15.38 months vs. 11.00 months, P = 0.56) on docetaxel for patients with no PSA decline, <50% decline and ≥ 50% decline on abiraterone respectively. Importantly, PSA response rates to docetaxel were comparable in the docetaxel‐experienced and docetaxel‐naïve cohorts and were not linked to prior response to abiraterone in either group. CONCLUSION Activity of docetaxel was not associated with the biochemical response to prior abiraterone therapy. These data suggest that prior response to abiraterone should not influence decisions on subsequent use of docetaxel in mCRPC. Prostate 74:1544–1550, 2014. © 2014 Wiley Periodicals, Inc.